1994
DOI: 10.1084/jem.180.2.745
|View full text |Cite
|
Sign up to set email alerts
|

T cell recognition of carbohydrates on type II collagen.

Abstract: SummaryA critical event in an immune response is the T cell recognition of peptides bound to major histocompatibility com~ex (MHC) molecules on the surface of an antigen presenting cell (APC). Although the majority of eukaryotic proteins are glycosylated, it has not yet been shown that T cell recognition of such proteins involves recognition of the bound carbohydrates. Type II collagen (CII), the major protein constituent of joint cartilage, is posttranslationally modified by hydroxylation and glycosylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
137
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 21 publications
5
137
0
Order By: Relevance
“…This results in smaller CII fragments being picked up by APC and presented by MHC class II. Previous studies from our laboratory showed that CII-specific T cells predominantly recognize glycosylation at position 264 in the CII260-270 epitope and that glycosylated CII is more arthritogenic than non-glycosylated CII is [3,11,13,20]. In addition, adoptive transfer of glycopeptidespecific T cells into CII-immunized DBA/1 mice increases the incidence and severity of arthritis as well as the production of CII-specific antibodies [21].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This results in smaller CII fragments being picked up by APC and presented by MHC class II. Previous studies from our laboratory showed that CII-specific T cells predominantly recognize glycosylation at position 264 in the CII260-270 epitope and that glycosylated CII is more arthritogenic than non-glycosylated CII is [3,11,13,20]. In addition, adoptive transfer of glycopeptidespecific T cells into CII-immunized DBA/1 mice increases the incidence and severity of arthritis as well as the production of CII-specific antibodies [21].…”
Section: Discussionmentioning
confidence: 84%
“…This T cell determinant contains lysine residues at position 264 and 270, which can become posttranslationally modified by hydroxylation and further galactosylated and glucosylated, creating many different epitopes containing hydroxyl, mono-and disaccharide groups in both RA and CIA. We have previously shown that autoreactive T cells predominantly recognize this epitope when it is posttranslationally modified at positions 264 and 270 by hydroxylation and further glycosylation [11][12][13]. The dominant T cell epitope is the side-chain of lysine at position 264 (K264) when the peptide is bound to A q , but when bound to DR4 the T cells recognize either position K264 or K270, although position 264 seems to be the more dominant of the two in this case.…”
Section: Introductionmentioning
confidence: 94%
“…We have previously shown the importance of galactosylation at position K 264 of CII259-273 for the immune recognition [12][13][14][15][16][17] and that CII in the healthy individuals is completely glycosylated at this position [16]. In line with these findings, an additional modification at position Q 267 by deamidation makes the study of the immune response more complex.…”
Section: Discussionmentioning
confidence: 55%
“…It is well established that during aging, inflammation, trauma or other pathologic processes, the frequency of posttranslational modifications, such as glycosylation, glycation, citrullination, oxidation, deamidation/transamidation or phosphorylation, is increased [10,11]. The role of glycosylated immunodominant CII260-270-peptide for development of autoimmune arthritis has been previously described [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation